Using Multimedia Technologies in Teaching English - Islomova X.F. (Zien Journals, 2023)
The article emphasizes the importance of using multimedia in the language teaching process in improving students' knowledge and developing oral speech
Keywords: use of modern multimedia tools; activation of cognitive activity of language learners; increasing students' interest in learning the language